O Direito Administrativo Sancionador e a individualização da conduta nas decisões dos Tribunais de Contas - Serrano, Antonio Carlos Alves Pinto (2019)
This study aims to explore the importance of the individualization of the conduct in the application of administrative sanctions resulting from decisions of the Court of Auditors. The analysis contemplates the Theory of Sanctioning Administrative Law as well as the role of the State and Public Administration regarding the jus puniendi, focusing that constitutional guarantee, reinforced on the principles of reasonability and proportionality. Considering the Brazilian republican model, the research will approach the division of the functions of power as well as the external and internal control, showing how the constitutional principles reflect on the sanctioning system, regarding both administrative and penal sanction, emphasizing the first. Taking into account all these elements, it will be addressed the functioning of the Courts of Auditors and how their decisions should be drafted considering the guarantee of the individualization of both conduct and penalty